Functional Outcomes of Total Ankle Arthroplasty at a Mean Follow-up of 7.6 Years: A Prospective, 3-Dimensional Gait Analysis. (17th March 2021) - Brodsky, James W.; Scott, Daniel J.; Ford, Samuel; Coleman, Scott; Daoud, Yahya
Abstract : Background: In vivo gait analysis provides objective measurement of patient function and can quantify that function before and after ankle reconstruction. Previous gait studies have shown functional improvement for up to 4 years following total ankle arthroplasty (TAA), but to date, there are no published studies assessing function at ≥5 years following TAA. We hypothesized that patients who underwent TAA would show significant improvements in walking function at a minimum follow-up of 5 years, compared with their preoperative function, as measured by changes in temporospatial, kinematic, and kinetic gait parameters. Methods: Three-dimensional gait analysis with a 12-camera digital motion-capture system and double force plates was utilized to record temporospatial, kinematic, and kinetic measures in 33 patients who underwent TAA with either the Scandinavian Total Ankle Replacement (Stryker; n = 28) or Salto Talaris Ankle (Integra LifeSciences; n = 5). Gait analysis was performed preoperatively and at a minimum follow-up of 5 years (mean, 7.6 years; range, 5 to 13 years). Results: Significant improvements were observed in multiple gait parameters, with temporospatial increases in cadence (+9.5 steps/min; p < 0.0001), step length (+4.4 cm; p = 0.0013), and walking speed (+0.2 m/s; p < 0.0001), and kinematic increases in total sagittal range of motion (+2.0°; p = 0.0263), plantar flexion at initial contact (+2.7°; p = 0.0044), and maximum plantar flexion (+2.0°; p = 0.0488). Kinetic analysis revealed no loss of peak ankle power, despite patients aging. Conclusions: To our knowledge, this is the first study to report 7-year functional outcomes of TAA, quantified by objective, in vivo measurements of patient gait. Patients were shown to have sustained improvement in multiple objective parameters of gait compared with preoperative function. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.